2013
DOI: 10.1177/070674371305800909
|View full text |Cite
|
Sign up to set email alerts
|

Validation de la traduction française de la SURPS pour une population d'adolescents québécois

Abstract: Objectif : La Substance Use Risk Profile Scale (SURPS) est un instrument de dépistage des caractéristiques de personnalité qui représentent un risque pour le développement d'une consommation problématique de substances. La SURPS comporte 23 items évaluant 4 dimensions et permet aux intervenants en santé mentale de mieux cibler la prévention. La SURPS a été validée au Canada anglais, au Royaume-Uni, en Chine et au Sri Lanka; l'objectif de cette étude est de valider une traduction française de la SURPS pour des … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
15
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 32 publications
2
15
0
2
Order By: Relevance
“…This applicability is because the internal consistencies of the SURPS-J were generally concordant with those obtained in previous studies (e.g., Malmberg et al, 2010). Additionally, other preceding studies (Castonguay-Jolin et al, 2013;Krank et al, 2011) also reported item 22 would be problematic. Furthermore, Study 2 demonstrated that the generally adequate testretest reliabilities ( Table 2).…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…This applicability is because the internal consistencies of the SURPS-J were generally concordant with those obtained in previous studies (e.g., Malmberg et al, 2010). Additionally, other preceding studies (Castonguay-Jolin et al, 2013;Krank et al, 2011) also reported item 22 would be problematic. Furthermore, Study 2 demonstrated that the generally adequate testretest reliabilities ( Table 2).…”
Section: Discussionsupporting
confidence: 53%
“…This scale has high cross-cultural validity, as demonstrated by studies conducted in England (Conrod & Woicik, 2002), Canada (Krank et al, 2011), the Netherlands (Malmberg et al, 2010), a French-speaking province in Canada (Castonguay-Jolin et al, 2013), Sri Lanka (Ismail, De Seneviratne, Newcombe, & Wanigaratne, 2009), and China (Siu, 2011). Additionally, the SURPS is a useful tool for screening individuals who are susceptible to drug reinforcement and substance use, and a number of studies using this measure have been conducted on a variety of samples, such as young people in child protective services (Stewart, McGonnell, Wekerle, Adlaf, & The MAP Longitudinal Study Research Team, 2011), adolescent samples (Mackie, Castellanos-Ryan, & Conrod, 2011), and imprisoned offenders (Brunelle, Douglas, Pihl, & Stewart, 2009;Hopley & Brunelle, 2012).…”
Section: Introductionmentioning
confidence: 88%
“…Taken together, these previous studies indicate that the SURPS can be a reliable tool for identifying high-risk personality profiles among adolescents with the aim of implementing selective programs to prevent substance misuse and other emotional and behavioural problems. In addition, the SURPS has demonstrated high cross-cultural validity, as evidenced by research carried out in the UK (22), the Netherlands (40,41), Canada (English and French versions) (31,42), Mexico (43), China (44), Sri Lanka (45), and Japan (46). Given the prevalence of substance use and the need for effective prevention among adolescents in Australia, the next important step is to examine the psychometric properties of the SURPS in an Australian adolescent sample.…”
Section: Introductionmentioning
confidence: 99%
“…Desde entonces, numerosos estudios han mostrado sus adecuadas propiedades psicométricas para la interpretación de las puntuaciones propuestas. Estos estudios han sido llevados a cabo en diferentes subpoblaciones, principalmente adolescentes (Ali et al, 2016;Castellanos-Ryan et al, 2013;Castonguay-Jolin et al, 2013;Chandrika, Seneviratne, Newcombe, y Wanigaratne, 2009;Jurk et al, 2015;Krank et al, 2011;Malmberg et al, 2010;Memetovic, Ratner, Gotay, y Richardson, 2016;Newton et al, 2015;Robles-García et al, 2014;Siu, 2010;Woicik et al, 2009) pero también con muestras de estudiantes universitarios (Omiya, Kobori, Tomoto, Igarashi, y Iyo, 2015), adultos (Canfield, Gilvarry, y Koller, 2015;Saliba, Moran, y Yoo, 2014), personas encarceladas (Anthony y Brunelle, 2016) y pacientes hospitalizados (Schlauch, Crane, Houston, y Lang, 2015). Estos estudios han replicado la estructura de 4 factores de la SURPS (Krank et al, 2011;Saliba et al, 2014;Schlauch et al, 2015) y han mostrado evidencias de validez convergente y discriminante Newton et al, 2015;Robles-García et al, 2014).…”
unclassified
“…La aplicabilidad de la SURPS se evidencia en el hecho de que ha sido traducida a diferentes idiomas como: sinhala (Chandrika et al, 2009), neerlandés (Malmberg et al, 2010), chino (Siu, 2010), coreano (Saliba et al, 2014), francés (Castonguay-Jolin et al, 2013;Jurk et al, 2015), alemán (Jurk et al, 2015), portugués (Canfield et al, 2015) y japonés (Omiya et al, 2015). La validación de la versión española de la SURPS (Robles-García et al, 2014) se realizó con 671 adolescentes mexicanos hispanohablantes (con edades entre 11-18 años).…”
unclassified